Fabrication and wear performance of (Cu–Sn) solution/TiCx bonded diamond composites - Baoyan, L.; Danhui, H.; Wangxi, Z. (Сверхтвердые материалы, 2018)
The Cu(Sn)–TiCx bonded diamond composites were prepared by in situ reaction sintering of Cu, Ti₂SnC and diamond powders. Effect of Ti₂SnC content on the phase composition, microstructure and grinding properties were studied. Вивчено вплив змісту Ti₂SnC на фазовий склад, мікроструктуру і шліфувальні властивості алмазних композитів зі зв’язуючим Cu(Sn)–TiCx, отриманих in situ реакційним спіканням Cu, Ti₂SnC і алмазних порошків. Изучено влияние содержания Ti₂SnC на фазовый состав, микроструктуру и шлифовальные свойства алмазных композитов со связующим Cu(Sn)–TiCx, полученных in situ реакционным спеканием Cu, T₂SnC и алмазных порошков.